Changes in morphologicalrheological blood properties of Hutnik Club football players - Kolbiarz, D.; Teleglów, A.; Scislowska-Czarnecka, A.; Marchewka, J.; Glodzik, J.; Zaba, K.; Filar-Mierzwa, K. (Journal of Kinesiology and Exercise Sciences, 2015)
Study aim. The aim of the study was to investigate the effect of long-term football training on the morphological-rheological properties of the blood. Study material. The study was conducted among a group of 16 footballers playing for the Hutnik Nowa Huta Club. The average age of subjects was 22 years. Practices are held 5 times a week, all year round with the exception of the last 3 weeks of December and the last 2 weeks of June. In addition, championship or sparring matches are played every weekend. Venous blood was collected at the end of the football season, in the morning on an empty stomach. Examination of morphological-rheological parameters of the blood was performed in the footballers and the control group. Results. Compared to the control group, a statistically significant decrease in RBC, HGB, HCT, MCV, PLT and plasma viscosity were found for the footballer group. And a statistically significant increase in fibrinogen and MCHC as well. There were no statistically significant changes in the amount of WBC and MCH. Significant changes were also noticed in erythrocyte aggregation and elongation for the footballers. AI reduced, while AMP and T½ increased. Elongation index at shear-stress for the range of 0.30-1.13 [Pa] significantly increased, while for the value ranges of 2.19-59.97 [Pa], a decrease was observed in this parameter. Conclusions. Long-term, regular football training does not cause pathological changes in the morphological-rheological properties of the blood.